2020
DOI: 10.1371/journal.pone.0241377
|View full text |Cite
|
Sign up to set email alerts
|

Drug-safety reporting in Polish nursing practice—Cross sectional surveys

Abstract: Introduction Nurses play a significant role in ensuring the safety and quality of drugs. Our aim was to assess significant factors in nurses’ participation in ensuring pharmacotherapy safety by reporting adverse drug reactions (ADR) and detecting substandard drugs (SD). Materials and methods The study was a cross-sectional, comparative survey, using original questionnaires. Survey questions were grouped to probe the opinions, attitudes and practices of nurses reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Our review findings indicate that although 67.1% of nurses encountered patients with ADR during their clinical practice, only a small percentage (21.2%) of them had the experience of ADR reporting. In several studies, nurses acknowledged that they were not adequately prepared to be capable to report ADRs [ 16 , 61 ]. Similar to our findings, a systematic review by Bhagavathula et al showed that 74.5% of Indian healthcare professionals including nurses never reported any ADRs [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our review findings indicate that although 67.1% of nurses encountered patients with ADR during their clinical practice, only a small percentage (21.2%) of them had the experience of ADR reporting. In several studies, nurses acknowledged that they were not adequately prepared to be capable to report ADRs [ 16 , 61 ]. Similar to our findings, a systematic review by Bhagavathula et al showed that 74.5% of Indian healthcare professionals including nurses never reported any ADRs [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…A key to creating a more robust surveillance culture is to ensure that all healthcare professionals who administer drugs are aware of how to monitor and report any difficulties that patients may experience [ 8 ]. Also involving physicians and pharmacists, nurses should additionally play a proactive role in PV activities and ADR reporting [ 16 ]. Nurses have a unique position in the healthcare team to monitor a patient's response to medication as they administer most drugs in healthcare settings and they are often present when an ADR happens and are involved in taking appropriate action to ameliorate the problem accordingly [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found in the literature. Many studies found a lack of pharmacovigilance knowledge among nurses [19][20][21][22]. An Indian study showed that more than half of health professionals are not aware of the national program of pharmacovigilance [23].…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly associated with the practices of PV in any healthcare system. However, literature has revealed that ADR reporting improved wherever there was an involvement of educational and training-based interventions including enhanced motivational strategies for reporting and enhanced availability of the reporting tools for the ADR reporting staff [12].…”
Section: Introductionmentioning
confidence: 99%